Miconia paralimoides (Miconieae: Melastomataceae), a new species from the Cordillera Central, Dominican Republic - Majure, Lucas Charles (Phytotaxa, 2013)
In the course of a taxonomic revision of Miconia sect. Lima, we discovered a previously undescribed species, Miconia paralimoides, from the Cordillera Central, Dominican Republic. This species is part of the Miconia lima species complex, and is most similar morphologically to Miconia limoides. We illustrate and provide a distribution map of the species, as well as a key to distinguish M. paralimoides from other members of the Miconia lima complex, i.e., species with very well-developed, bulla-based hairs on the adaxial leaf surface, which mostly or completely cover the areoles.